Exercise and fall prevention self-management to reduce mobility-related disability and falls after fall-related lower limb fracture in older people: protocol for the RESTORE (Recovery Exercises and STepping On afteR fracturE) randomised controlled trial. Issue 1 (December 2016) - Sherrington, Catherine; Fairhall, Nicola; Kirkham, Catherine; Clemson, Lindy; Howard, Kirsten; Vogler, Constance; Close, Jacqueline; Moseley, Anne; Cameron, Ian; Mak, Jenson; Sonnabend, David; Lord, Stephen
Abstract Background Lasting disability and further falls are common and costly problems in older people following fall-related lower limb and pelvic fractures. Exercise interventions can improve mobility after fracture and reduce falls in older people, however the optimal approach to rehabilitation after fall-related lower limb and pelvic fracture is unclear. This randomised controlled trial aims to evaluate the effects of an exercise and fall prevention self-management intervention on mobility-related disability and falls in older people following fall-related lower limb or pelvic fracture. Cost-effectiveness of the intervention will also be investigated. Methods/Design A randomised controlled trial with concealed allocation, assessor blinding for physical performance tests and intention-to-treat analysis will be conducted. Three hundred and fifty people aged 60 years and over with a fall-related lower limb or pelvic fracture, who are living at home or in a low care residential aged care facility and have completed active rehabilitation, will be recruited. Participants will be randomised to receive a 12-month intervention or usual care. The intervention group will receive ten home visits from a physiotherapist to prescribe an individualised exercise program with motivational interviewing, plus fall prevention education through individualised advice from the physiotherapist or attendance at the group based "Stepping On" program (seven two-hour group sessions). Participants will be followed for a 12-month period. Primary outcome measures will be mobility-related disability and falls. Secondary outcomes will include measures of balance and mobility, falls risk, physical activity, walking aid use, frailty, pain, nutrition, falls efficacy, mood, positive and negative affect, quality of life, assistance required, hospital readmission, and health-system and community-service contact. Discussion This study will determine the effect and cost-effectiveness of this exercise self management intervention on mobility-related disability and falls in older people who have recently sustained a fall-related lower limb or pelvic fracture. The results will have implications for the design and implementation of interventions for older people with fall related lower limb fractures. The findings of this study will be disseminated in peer-reviewed journals and through professional and scientific conferences. Trial Registration Australian New Zealand Clinical Trials Registry:ACTRN12610000805077 .